A History of Preterm Delivery Is Associated with Aberrant Postpartal MicroRNA Expression Profiles in Mothers with an Absence of Other Pregnancy-Related Complications - Hromadnikova, Ilona; Kotlabova, Katerina; Krofta, Ladislav (International journal of molecular sciences, 2021)
This prospective cross-sectional case-control study investigated the postpartal gene expression of microRNAs associated with diabetes/cardiovascular/cerebrovascular diseases in the peripheral white blood cells of women with anamnesis of preterm prelabor rupture of membranes (n = 58), spontaneous preterm birth (n = 55), and term delivery (n = 89) by a quantitative reverse transcription polymerase chain reaction. After pregnancies complicated by preterm prelabor rupture of membranes or spontaneous preterm birth, mothers showed diverse expression profiles for 25 out of 29 tested microRNAs (miR-1-3p, miR-16-5p, miR-17-5p, miR-20a-5p, miR-20b-5p, miR-21-5p, miR-23a-3p, miR-24-3p, miR-26a-5p, miR-29a-3p, miR-100-5p, miR-103a-3p, miR-125b-5p, miR-126-3p, miR-130b-3p, miR-133a-3p, miR-143-3p, miR-145-5p, miR-146a-5p, miR-181a-5p, miR-195-5p, miR-199a-5p, miR-221-3p, miR-499a-5p, and miR-574-3p). The earliest gestational ages at delivery and the lowest birth weights of newborns were associated with the highest postpartal levels of the previously mentioned microRNAs in maternal peripheral white blood cells. Administration of tocolytic drugs in order to prolong pregnancy, used in order to administer and complete a full course of antenatal corticosteroids, was associated with alterations in postpartal microRNA expression profiles to a lesser extent than in women with imminent delivery, where there was insufficient time for administration of tocolytics and antenatal corticosteroids. Overall, mothers who did not receive tocolytic therapy (miR-24-3p and miR-146a-5p) and mothers who did not receive corticosteroid therapy (miR-1-3p, miR-100-5p, and miR-143-3p) had increased or showed a trend toward increased postpartal microRNA expression when compared with mothers given tocolytic and corticosteroid therapy. In addition, mothers with serum C-reactive protein levels above 20 mg/L, who experienced preterm labour, showed a trend toward increased postpartal expression profiles of miR-143-3p and miR-199a-5p when compared with mothers with normal serum C-reactive protein levels. On the other hand, the occurrence of maternal leukocytosis, the presence of intra-amniotic inflammation (higher levels of interleukin 6 in the amniotic fluid), and the administration of antibiotics at the time of preterm delivery had no impact on postpartal microRNA expression profiles in mothers with a history of preterm delivery. Likewise, the condition of the newborns at the moment of birth, determined by Apgar scores at 5 and 10 min and the pH of cord arterial blood, had no influence on the postpartal expression profiles of mothers with a history of preterm delivery. These findings may contribute to explaining the increased cardiovascular risk in mothers with anamnesis of preterm delivery, and the greater increase of maternal cardiovascular risk with the decrease of gestational age at delivery. Women with preterm delivery in their anamnesis represent a high-risk group with special needs on a long-term basis, with a need to apply preventive and therapeutic interventions as early as possible.
Keywords: Premature Birth; dospělí; Cerebrovascular Disorders; předčasný porod; Female; předčasný odtok plodové vody; C-Reactive Protein; novorozenec; Birth Weight; Adult; ženské pohlaví; Postpartum Period; Reproducibility of Results; lidé; Infant, Newborn; porodní hmotnost; Pilot Projects; těhotenství; vedení porodu; pilotní projekty; studie případů a kontrol; signální transdukce; stanovení celkové genové exprese; Signal Transduction; Fetal Membranes, Premature Rupture; leukocyty; regulace genové exprese; reprodukovatelnost výsledků; matky; Cardiovascular Diseases; Case-Control Studies; Delivery, Obstetric; Mothers; komplikace těhotenství; mikro RNA; Leukocytes; kardiovaskulární nemoci; cerebrovaskulární poruchy; MicroRNAs; lidé středního věku; C-reaktivní protein; Pregnancy Complications; poporodní období; Gene Expression Regulation; Pregnancy; Middle Aged; Gene Expression Profiling; Humans